Fluorescent carbon dots based on ampicillin sodium as well as preparation method and application of fluorescent carbon dots

By preparing water-soluble N-doped fluorescent carbon dots (ACDs), using them to perform multivariate sensing detection of Fe3+ and Cu2+, the problem of expensive and complex operation of Fe3+ and Cu2+ detection methods in the prior art is solved, and efficient and sensitive The detection effect provides good prospects for real-time monitoring of environmental and biological systems.

CN119505891AActive Publication Date: 2025-02-25SHANDONG INST OF PARASITIC DISEASES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411653291.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

The prior art methods for detecting Fe3+ and Cu2+ are expensive and complex in operation, limiting their practical application in environmental and medical applications.

Method used

Water-soluble N-doped fluorescent carbon dots (ACDs) were prepared by dissolving sodium ampicillin in water, and then subjecting to solubilizing carbonization after ultrasonic treatment, and using it to perform multivariate sensing detection of Fe3+ and Cu2+.

Benefits of technology

The prepared ACDs exhibit excellent optical behavior, light stability and water solubility, with detection limits of 0.31μM and 0.26μM respectively. They can effectively detect real water samples in the environment and Fe3+ and Cu2+ in cells, making it a Fe3+ in the environment and biological system. Real-time monitoring of Cu2+ provides good prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005141516640000011
    Figure HDA0005141516640000011
  • Figure HDA0005141516640000012
    Figure HDA0005141516640000012
  • Figure HDA0005141516640000013
    Figure HDA0005141516640000013
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of carbon-based materials, and particularly relates to a fluorescent carbon dot based on ampicillin sodium as well as a preparation method and application of the fluorescent carbon dot. The preparation method comprises the following steps: dispersing ampicillin sodium in distilled water, carbonizing the ampicillin sodium by a solvothermal method, and separating and purifying to obtain the water-soluble N-doped fluorescent carbon dots emitting blue fluorescence. The prepared carbon dots show excellent optical behaviors, excellent light stability and excellent water solubility. The prepared carbon dots can be used for detecting Fe < 3 + > and Cu < 2 + > in real environment water samples and living cells, and are good in selectivity and high in sensitivity. Compared with other carbon dot-based fluorescence sensing methods, the detection method provided by the invention is equivalent to or better than other carbon dot-based fluorescence sensing methods.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon-based material preparation, and specifically relates to a fluorescent carbon dot based on ampicillin sodium and a preparation method and application thereof. Background Art

[0002] Heavy metal ion pollution includes iron, copper, lead, cadmium, etc., which poses a huge threat to human health, agricultural production and the environment. 3+ It is the most abundant essential trace element in the human body. It plays an extremely important role in many biological processes, including oxygen binding and transportation, cell proliferation and differentiation, DNA repair, photosynthesis, electron transfer, etc. 3+ It will affect the hemoglobin synthesized by red blood cells, resulting in a decrease in the volume and oxygen-carrying capacity of red blood cells, leading to iron deficiency anemia. In addition, excess Fe 3+ It can cause arteriosclerosis, physiological and metabolic disorders, etc. 2+ As another important element in the human body, it maintains the cellular respiratory system, bone formation redox process and biosynthesis. 2+ Both insufficiency and excess can lead to a range of serious health disorders, such as Alzheimer's disease, Men's disease, Wilson's disease and Parkinson's disease. 3+ and Cu 2+ The maximum allowable concentrations of 0.3 mg / L and 1.3 mg / L, respectively. Therefore, the design of the synthesis of Fe 3+ and Cu 2+ Probe for Fe in environmental and medical applications 3+ and Cu 2+ It is of great significance to conduct fast and accurate visual detection.

[0003] Currently, the Fe 3+ and Cu 2+ The main methods for the detection of ions include mass spectrometry, X-ray fluorescence spectroscopy, voltammetry, electrochemical method, etc. However, the expensive instrument and operation costs, as well as the complicated pretreatment process limit their practical application. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a method for preparing ampicillin carbon dots, comprising the following steps:

[0005] (1) dissolving ampicillin sodium in water, ultrasonically treating the mixture for 30 minutes, and then reacting the mixture at 180° C. for 12 hours. After cooling, a yellow suspension was obtained;

[0006] (2) filtering the yellow suspension with a 0.22 μm filter membrane, placing the filtered solution in a dialysis bag and dialyzing it for 24 hours to obtain a purified solution;

[0007] (3) The purified solution was freeze-dried for 24 h to obtain ampicillin carbon dot powder.

[0008] Furthermore, the mass volume ratio of ampicillin sodium and water in step (1) is 0.56 g:30 mL.

[0009] Furthermore, the reaction conditions in step (1) are to carry out the reaction in a polytetrafluoroethylene-lined autoclave.

[0010] Furthermore, the dialysis molecular weight cutoff in step (2) is 500 Da.

[0011] The present invention also provides an ampicillin carbon dot, which is prepared by the above preparation method.

[0012] The present invention also provides the above-mentioned ampicillin carbon dots for detecting real environmental water samples and intracellular Fe 3+ and Cu 2+ Application in this area.

[0013] The present invention has the following beneficial effects:

[0014] The present invention disperses ampicillin sodium in distilled water, then carbonizes the ampicillin sodium by a solvothermal method, separates and purifies it, and obtains water-soluble N-doped fluorescent carbon dots (ACDs) with blue fluorescence emission. The prepared ACDs exhibit excellent optical behavior, excellent photostability, and excellent water solubility. Based on the synergistic effect of the internal filter effect (IFE) and static quenching, the ACDs are used to 3+ and Cu 2+ The detection limits of the multi-sensor were 0.31 μM and 0.26 μM, respectively. 3+ and Cu 2+ These findings confirm that the proposed ACDs can be used as fluorescent sensors for Fe 3+ and Cu 2+ Effective detection of Fe in environmental and biological systems 3+ and Cu 2+ Real-time monitoring provides a good prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0016] Figure 1 (a) UV absorption and fluorescence spectra of ACDs, with the insets showing images of ACDs under visible light (left) and UV light (right); (b) Emission spectra of ACDs under different excitations;

[0017] Figure 2 (a) ACDsTEM image (the inset is the HRTEM image and size distribution diagram); (b) FT-IR image; (c) XPS full spectrum; (d) C1s; (e) N 1s and (f) O 1s spectra;

[0018] Figure 3 (a) Effect of different pH values ​​on ACDs fluorescence; (b) Effect of different concentrations of NaCl solution on ACDs fluorescence;

[0019] Figure 4 (a) Fluorescence emission spectra of ACDs solution with different ions added; (b) Relative fluorescence intensity of ACDs solution with different ions added; (c) UV light irradiation images of ACDs solution with different ions added;

[0020] Figure 5 (a) Different concentrations of Fe 3+ Fluorescence spectrum after adding ACDs; (b) F 0 / F and Fe 3+ Linear relationship between concentrations (0.9-80μM); (c) Different concentrations of Cu 2+ Fluorescence spectrum after adding ACDs; (b) F 0 / F and Cu 2+ Linear relationship between concentrations (0.8-90 μM);

[0021] Figure 6 Other metal ions (100 μM) for detection of (a) Fe 3+ and (b) Cu 2+ interference;

[0022] Figure 7 The cytotoxicity of ACDs at different concentrations (0-1000 μg / mL) on HeLA cells; (b) ACDs, ACDs-Fe 3+ and ACDs-Cu 2+ Bright field and fluorescence images of HeLa cells treated with the complex;

[0023] Figure 8 Quenching mechanism diagram of ACD. (a) Adding Fe into ACDs solution 3+ and Cu 2+ The fluorescence lifetime of Fe 3+ and Cu 2+ Overlap of the UV absorption spectrum of and the fluorescence spectrum of ACDs; (c) ACDs, Fe 3+ , Cu 2+ And different concentrations of Fe were added to ACDs 3+ and Cu 2+ The UV absorption spectrum after . DETAILED DESCRIPTION

[0024] Now, various exemplary embodiments of the present invention are described in detail. The methods in the examples are conventional methods unless otherwise specified, and the reagents used are conventional commercially available reagents or reagents prepared by conventional methods unless otherwise specified. This detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, features and embodiments of the present invention.

[0025] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0026] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0027] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0028] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0029] Example 1

[0030] 1.1 Synthesis of Ampicillin Carbon Dots (ACDs)

[0031] ACDs were synthesized by a one-step hydrothermal method using sodium ampicillin as the raw material. First, 0.56 g of sodium ampicillin was dissolved in 30 ml of water and ultrasonically treated for 30 minutes. The mixture was then placed in a polytetrafluoroethylene-lined autoclave and reacted at 180°C for 12 hours. A yellow suspension was obtained after cooling. The yellow suspension was then filtered with a 0.22 μm filter membrane to remove larger particles or undissolved impurities. The filtered solution was placed in a dialysis bag (molecular weight cutoff of 500 Da) and dialyzed for 24 hours to remove unreacted raw materials and smaller impurities. Finally, the dialyzed purified solution was freeze-dried for 24 hours to obtain dry ACDs powder.

[0032] 1.2Fe 3+ and Cu 2+ Detection

[0033] Fe 3+ and Cu 2+ The construction of the detection method is based on selective experiments. In order to study the application of ACDs in ion detection, common metal ions (K + ,Ag + ,Na + ,Fe 3+ ,Zn 2+ ,Al 3+ ,Mn 2+ ,Pb 2+ Mg 2+ ,Cu 2+ ,Cr 3+ ,Hg 2+ and Co 2+ ) was prepared into a 0.1M solution, and 10 μL of the metal ion solution was mixed with 990 μL ACDs (100 μg / mL) solution, and the fluorescence spectrum of the mixed solution before and after the addition of ions was recorded within the excitation wavelength range of 350 nm, and the corresponding fluorescence emission intensity was recorded at 450 nm. 3+ and Cu 2+ The effects of ACDs on Fe 3+ and Cu 2+ All fluorescence measurements were performed at room temperature. The limit of detection was estimated using the formula LOD = 3σ / K, where “σ” is the standard deviation of the blank sample and “K” is the slope of the standard curve.

[0034] 1.3 Cytotoxicity and bioimaging of ACDs

[0035] The cytotoxicity of ACDs was studied using the CCK-8 detection kit, and HeLa cells were selected as the cell line. HeLa cells were cultured to the logarithmic growth phase, seeded into 96-well plates with a cell density of 5000 cells per well, and cultured overnight in an incubator at 37°C with 5% CO2. After 24 hours, the cells were treated with 100 μL of fresh Dulbecco's Modified Eagle Medium (DMEM), which contained 0, 50, 100, 150, 200, 400, 800, and 1000 μg / mL of ACDs. After incubation for 24 hours, each well was washed three times with PBS (0.01 M, pH 7.4). Then 100 μL of culture medium and 10 μL of CCK-8 were added to each well. After the 96-well cell culture plate was placed in the incubator for 1 hour, the OD value was measured at 450 nm using a microplate reader. The survival rate of HeLa cells was calculated based on the OD value.

[0036] For cell imaging, HeLa cells were seeded on 24-well plates at a density of 5,000 cells per well and incubated for 24 hours. Next, 500 μL ACDs solution (100 ug / mL) was added and further incubated for 12 hours. Fe 3+ and Cu 2+ Incubate for 2 hours. Then, wash the cells three times with PBS. Finally, observe the cells using a fluorescence microscope.

[0037] Example 2 Results and Discussion

[0038] 2.1 Characterization of ACDs

[0039] The optical properties of ACDs are mainly studied through UV-visible absorption spectroscopy and fluorescence spectroscopy. ACDs aqueous solution is light yellow and emits bright blue fluorescence under 365nm ultraviolet light ( Figure 1 a illustration). In the UV-visible absorption spectrum, Amp shows an obvious absorption peak at 264nm. After Amp is converted into ACDs product, the absorption peak moves from 264nm to 251nm, which can be attributed to the π-π bond of C=C. * The strong absorption of ACDs at 350nm is due to the n-π* transition of C=O bond, and the fluorescence excitation band of ACDs overlaps with its absorption band at 350nm. Figure 1 b is the fluorescence behavior of ACDs under different excitation wavelengths (290-400nm). When the excitation wavelength changes from 290nm to 400nm, the position of the maximum emission peak shows a slight red shift, and when the excitation wavelength is 350nm, the fluorescence intensity of ACDs reaches the maximum value.

[0040] From transmission electron microscopy Figure 2 a It can be seen that the ACDs are approximately spherical and have good dispersion in water. From the high-resolution TEM image, lattice fringes with a lattice spacing of 0.20 nm can be clearly seen, which is consistent with the lattice fringes on the surface of graphite carbon (100) structure. Figure 2 a Illustration shows the particle size statistics of ACDs particles, with a particle size range of 3-5.8 nm and an average size of 4.6 nm.

[0041] The characteristic peaks of ACDs in FT-IR ( Figure 2 b), we can know the main functional groups on the surface of ACDs. ACD and Amp are at 3500-3100cm -1 There are strong and broad absorption peaks in the range of 1620-1770cm, which is consistent with the stretching vibration of OH and NH, which can be attributed to the intermolecular hydrogen bonds in Amp and ACD. -1 The peak at 1400-1460 cm is attributed to the stretching vibration of C=O, C=C and the bending vibration of NH; -1 The peaks at correspond to CN and CH. The NH bending vibration peak in the Amp spectrum is about 1770 cm -1 and 1690cm -1 However, it disappeared in the ACD spectrum. This may be due to the C=C (1630 -1 ) tensile vibration.

[0042] XPS spectra show that ACDs have three obvious peaks at ~284 (C1s), ~400 (N1s), and ~532 eV (O1s). Figure 2 c) If Figure 2 As shown in the inset of c, the percentages of C, N, and O in ACD are 61.86%, 9.29%, and 28.85%, respectively. C1s spectrum ( Figure 2 d) shows that the ACD surface contains three different types of carbon atoms: CC / C=C (284.0 eV), CN / CO (284.9 eV) and C=O (287.6 eV). Figure 2 The N1s spectrum in e has analytical peaks at 399.0eV and 400.5eV, corresponding to pyrrolic N and graphitic N, respectively. The O1s spectrum ( Figure 2 f) There are absorption peaks at 530.4eV and 531.1eV, corresponding to C=O and CO, respectively. The XPS analysis results are consistent with FT-IR. The characterization results show that there are hydrophilic groups such as hydroxyl, amino, and carboxyl groups on the surface of ACDs.

[0043] 2.2 Stability study of ACDs

[0044] The stability of fluorescent materials often greatly affects their applications in real environments. Therefore, we investigated the effects of pH and ionic strength on the stability of ACDs. Figure 3 As shown in a, the fluorescence intensity of the ACD solution shows different responses at different pH values ​​(1-12). As the pH value (1-10) increases, the fluorescence intensity gradually increases, while when the pH value is greater than 10, the fluorescence intensity does not change significantly. The pH responsiveness of ACDs may be related to the presence of amines on the surface of ACDs. Amines react with acids as Lewis bases to form ammonium salts, thereby destroying the surface state of ACDs and causing the fluorescence intensity of ACDs to be quenched under acid conditions. Figure 3 As shown in (b), when the NaCl concentration is 1 M, the fluorescence intensity of ACD does not change, indicating that ACD can emit stably even under high salt conditions. This shows that the fluorescence properties of ACD are not affected by changes in the surrounding ion environment. This stability is beneficial to the potential applications of ACD.

[0045] 2.3 ACDs to Fe 3+ and Cu 2+ Detection

[0046] The oxygen-containing functional groups on the surface of ACDs can improve their water solubility, and due to the coordination between oxygen functional groups and metal ions, ACDs have the potential for application in metal ion detection. Therefore, we studied the effects of various metal ions on the fluorescence intensity of ACDs. Figure 4 As shown in (a and b), when 100 M of different cations K are added + 、Ag + 、Na + 、Zn 2+ 、Al 3+ , Mn 2+ , Pb 2+ Mg 2+ Cr 3+ , Hg 2+ and Co 2+ When the fluorescence intensity of ACD does not change, only Fe 3+ and Cu 2+ The fluorescence intensity of ACD can be significantly reduced, which may be due to the presence of a large number of oxygen-containing functional groups on the surface of ACDs, especially carboxyl and hydroxyl groups. In addition, it can be clearly observed that after the removal of Cu 2+ and Fe 3+ In the presence of all metal ions except , the blue fluorescence of ACD under UV light remains unchanged ( Figure 4 c) These results show that ACDs are effective in detecting Cu 2+ and Fe 3+ Highly selective.

[0047] Furthermore, the effects of ACDs on Fe 3+ and Cu 2+ The fluorescence response curve of Figure 5 a and Figure 5 c It can be seen that at the best emission peak of ACDs at 450nm, as Fe 3+ and Cu 2+ As the concentration gradually increases, the fluorescence intensity of the ACDs solution gradually decreases. Figure 5 As shown in b, Fe 3+ The fluorescence response of ACDs to the concentration ranged from 0.9 to 80 μM showed a good linear relationship, and the correlation coefficient (R 2 ) is 0.9956, and the linear equation is F 0 / F=1.01264+0.01193C Fe 3+ Among them, F 0 and F are respectively the addition of Fe 3+ Fluorescence intensity before and after. 2+ ,like Figure 5 d, Cu 2+ The fluorescence response of ACDs to the concentration ranged from 0.8 to 90 μM showed a good linear relationship, and the correlation coefficient (R 2 ) is 0.9932, and the linear equation is F 0 / F=1.03775+0.0146C Cu 2+ The detection limits of Fe in drinking water are 0.31μM and 0.26μM respectively, which are lower than the above-mentioned limits. 3+ (5.37 μM) and Cu 2+ Tables 1 and 2 summarize the currently published studies on Fe 3+ and Cu 2+ Some literature on fluorescence sensors. Obviously, Fe 3+ and Cu 2+ The fluorescence sensors performed on par or better than previously published sensors.

[0048] In order to further understand the practical application of ACDs 3+ and Cu 2+ The applicability of the assay was investigated by interference experiments with some coexisting metal ions (100 μM). Figure 6 As shown in a and b, the coexistence of other ions has an important effect on Fe 3+ / Cu 2+ These results confirm that ACDs can be used as fluorescent probes to sense Fe in aqueous environments. 3+ and Cu 2+ High selectivity.

[0049] 2.4 Cytotoxicity and bioimaging studies of ACDs

[0050] As a potential biomarker reagent, the cytotoxicity and biocompatibility of ACDs must be considered. The MTT method was used to determine the cytotoxicity of ACDs. Figure 7 As shown in a, after HeLa cells were treated with 1000 μg / mL ACDs for 24 h, the cell viability remained above 90%, indicating that ACDs have low cytotoxicity and good application prospects, and can therefore be used for biological imaging.

[0051] Fluorescence imaging of ACDs was then used to evaluate Fe 3+ and Cu 2+ Visualization of Figure 7 As shown in b, ACDs did not significantly change or damage the cell shape, indicating that ACDs have relatively low toxicity and good biocompatibility. The cells were excited and observed in the blue, green, and red channels, respectively, and it was found that the cells only emitted bright blue fluorescence, while green and red fluorescence were negligible. 3+ and Cu 2+ Treat cells for 30 min to study Fe 3+ and Cu 2+ Effects on cell fluorescence imaging. Studies have found that adding Fe 3+ and Cu 2+ After PCR, the fluorescence of the cells was significantly quenched, but the cell morphology remained good. These findings indicate that ACDs have good membrane permeability and can be used to label Fe 3+ and Cu 2+ .

[0052] 2.5 Testing of actual samples

[0053] In order to verify the feasibility of ACDs in detecting real samples, Fe 3+ and Cu 2+ As shown in Table 3, Fe in tap water and drinking water 3+ and Cu 2+ The recoveries ranged from 98.00% to 102.40%, and the corresponding relative standard deviations (RSDs) were less than 4.42%. These results indicate that the synthesized ACDs can be used as a novel method for detecting Fe in real samples. 3+ and Cu 2+ good candidate for .

[0054] 2.6ACDs to Fe 3+ and Cu 2+ Detection mechanism

[0055] Fe 3+ / Cu 2+ The fluorescence quenching of ACDs may be caused by dynamic or static quenching, photoinduced electron transfer, inner filter effect (IFE) or fluorescence resonance energy transfer (FRET). 3+ and Cu 2+ First, we measured and compared the ACDs and Fe 3+ / Cu 2+ The fluorescence lifetime before and after mixing. Figure 8 As shown in a, in Fe 3+ and Cu 2+ The fluorescence lifetime curves of ACDs in the presence or absence of Fe show negligible changes, with average lifetimes of 4.25 ns, 4.38 ns, and 4.90 ns, respectively. 3+ and Cu 2+ The fluorescence quenching of ACDs is not caused by FRET and single dynamic quenching, but a static quenching process.

[0056] from Figure 8 b found Fe 3+ There is a partial spectral overlap between the absorption spectrum of Fe and the excitation spectrum of ACDs, indicating that Fe 3+ The fluorescence quenching of ACDs may be caused by IFE. 2+ There is no absorption in the band studied, so Cu 2+ The fluorescence quenching of ACDs was not caused by the inner filter effect. Next, the UV-visible absorption spectra were analyzed to further investigate the Fe 3+ and Cu 2+ The fluorescence quenching mechanism of ACDs. Figure 8 As shown in c, Fe 3+ and Cu 2+ After treatment, no new absorption peaks were found in the UV spectrum of ACDs. 3+ / Cu 2+ The absorbance of the reaction mixture is not ACDs and Fe 3+ / Cu 2+ -absorbance values, but rather an enhancement based on this. This may be due to the non-fluorescent ACDs-Fe 3+ and ACDs-Cu 2+ Formation of ground state complex

[0057] Taking all factors into consideration, Fe 3+ The fluorescence quenching of ACDs is mainly attributed to IFE and ACDs-Fe 3+ The formation of non-fluorescent complexes, but Cu 2+ The fluorescence quenching of ACDs is due to the ACDs-Cu 2+ Formation of non-fluorescent composites.

[0058] in conclusion

[0059] Water-soluble carbon dots were synthesized by a one-step hydrothermal method using AMP as the only precursor. The obtained ACDs are uniformly sized spherical particles with an average particle size of 4.6 nm, which can exhibit bright blue fluorescence under ultraviolet light. The quality of the produced ACDs can be confirmed by comprehensive characterization of its properties using UV-visible spectroscopy, fluorescence spectroscopy, Fourier transform infrared spectroscopy, transmission electron microscopy and X-ray photoelectron spectroscopy analysis. Further studies have shown that due to the non-fluorescent complex ACDs-Fe 3+ and ACDs-Cu 2+ The formation of Fe 3+ and Cu 2+ The FL intensity of ACDs was greatly quenched. The fluorescence intensity of ACDs was related to Fe 3+ (0.9 to 80 μM) and Cu 2+ (0.8 to 90 μM) concentrations showed a good linear relationship, Fe 3+ and Cu 2+ The detection limits of 2 and 3 μM were 0.31 μM and 0.26 μM, respectively. In addition, the designed ACD fluorescent probe can be applied to the determination of Fe in water samples. 3+ and Cu 2+ , with recoveries ranging from 98.00% to 102.40%. It is noteworthy that ACDs are very suitable for the Fe3+ and Cu 2+ Visualization. Therefore, the developed ACD has potential application prospects in cell imaging and environmental monitoring. The above-mentioned embodiments are only descriptions of the preferred embodiments of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solution of the present invention by ordinary technicians in this field should fall within the scope of protection determined by the claims of the present invention.

Claims

1. A method for preparing ampicillin carbon dots, characterized in that: The following steps are involved: (1) dissolving ampicillin sodium in water, ultrasonically treating the mixture for 30 minutes, then reacting the mixture at 180° C. for 12 hours, and cooling the mixture to obtain a yellow suspension; (2) filtering the yellow suspension with a 0.22 μm filter membrane, placing the filtered solution in a dialysis bag and dialyzing it for 24 hours to obtain a purified solution; (3) The purified solution was freeze-dried for 24 h to obtain ampicillin carbon dot powder.

2. The preparation method according to claim 1, characterized in that: The mass volume ratio of ampicillin sodium and water in step (1) is 0.56 g:30 mL.

3. The preparation method according to claim 1, characterized in that: The reaction conditions in step (1) are to carry out the reaction in a polytetrafluoroethylene-lined autoclave.

4. The preparation method according to claim 1, characterized in that: The dialysis molecular weight cutoff in step (2) is 500 Da.

5. An ampicillin carbon dot, characterized in that: Prepared by any one of the preparation methods of claims 1-4.

6. The ampicillin carbon dots as claimed in claim 5 are used to detect real environmental water samples and intracellular Fe 3+ and Cu 2+ Application in this area.